Macroalgae detritus accelerates degradation of recalcitrant organic matter in coastal marine sediments - Julie Lyhne Ehrenreich; Annette Bruhn; Daniel Taylor; Mette Møller Nielsen; Peter Søndergaard Schmedes; Line Hermannsen; Birgit Olesen; Teis Boderskov; Signe Høgslund (Marine Pollution Bulletin, 2026)

Blue Mussels (Mytilus edulis) Improve Light Conditions in a Downstream Eelgrass (Zostera marina) Meadow in the Limfjorden, Denmark - Emil Hoffmann Bohr; Daniel Taylor; Tobias Kuhlmann Andersen; Aris Thomasberger; Mollie Elizabeth Brooks; Line Hermannsen; Karen Timmermann (Estuaries and Coasts, 2026)
Eelgrass ( Zostera marina ) constitutes critical habitat worldwide in terms of ecosystem services and biodiversity, yet less than 30% coverage remains in Danish waters compared to historical records. Persistent eutrophication has substantially reduced water clarity, making light the primary limiting factor for the distribution of eelgrass. Through particle filtration, filter-feeders such as blue mussels ( Mytilus edulis ) can influence light conditions in coastal habitats. This study hypothesized that blue mussel beds could improve light conditions within nearby eelgrass meadows and thus facilitate eelgrass growth. Light and current data were gathered from 37 sampling stations in three different habitats (eelgrass meadows, blue mussel beds, and mixed) at two sites in a shallow estuary in the Limfjorden, Denmark, characterized by different mussel–eelgrass configurations from May to September 2023. Across the three habitats, the light attenuation coefficient for photosynthetically active radiation, K d (PAR), was generally lower above blue mussel beds compared to eelgrass meadows and mixed habitats, likely due to suspended particle filtration by the mussels. Further supporting that mussels improved light conditions, median K d (PAR) in the eelgrass was lower when the eelgrass meadows were downstream from the mussel beds, than for the opposite current direction. Using state-space models, temporal changes in K d (PAR) were shown to be predominantly controlled by seasonal changes in chlorophyll a concentration in Lovns Broad, whereas current velocity only had minor impact. These findings suggest that blue mussels can improve water clarity in adjacent eelgrass meadows, likely alleviating light limitation and thereby supporting eelgrass growth and ecosystem functioning.

Commercial scale cultivation of Saccharina latissima in Denmark: Biomass yield, production costs, and environmental effects - Mette Møller Nielsen; Line Hermannsen; Teis Boderskov; Daniel Taylor; Peter Søndergaard Schmedes; Annette Bruhn (Algal Research, 2026)

Quantifying marine traffic intensity in Northwest Greenland and the potential disturbance of two seabird colonies - Flemming Ravn Merkel; Aili Lage Labansen; Thyge Feldskou Autzen; Malene Simon; Line Hermannsen (Marine Pollution Bulletin, 2023)